2020
DOI: 10.1186/s43008-020-00043-x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Botryosphaeriaceae from Eucalyptus plantations in YunNan Province in southwestern China across a climatic gradient

Abstract: The Botryosphaeriaceae accommodates many important pathogens of woody plants, including Eucalyptus. Recently, Botryosphaeriaceae were isolated from diseased plant parts from surveys of Eucalyptus plantations in the YunNan Province, China. The aims of this study were to identify these Botryosphaeriaceae isolates and to evaluate their pathogenicity to Eucalyptus. A total of 166 isolates of Botryosphaeriaceae were obtained from six regions in the YunNan Province, of which 76 were from Eucalyptus urophylla × E. gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 114 publications
0
27
0
1
Order By: Relevance
“…in Iran [ 16 ]. Species of Diplodia , Dothiorella , Lasiodiplodia , and Neofusicoccum detected in our study are widely reported as pathogens of other host plants in Algeria and Tunisia [ 39 , 40 ], Australia [ 41 ], Brazil [ 42 ], China [ 43 , 44 ], Chile [ 45 ], Italy, Portugal [ 39 , 46 , 47 , 48 ], South Africa [ 49 ], and the USA [ 13 , 31 , 36 ]. The results obtained in our study provide valuable information related to the richness, occurrence, and pathogenicity of Botryosphaeriaceae species in association with citrus species.…”
Section: Discussionmentioning
confidence: 86%
“…in Iran [ 16 ]. Species of Diplodia , Dothiorella , Lasiodiplodia , and Neofusicoccum detected in our study are widely reported as pathogens of other host plants in Algeria and Tunisia [ 39 , 40 ], Australia [ 41 ], Brazil [ 42 ], China [ 43 , 44 ], Chile [ 45 ], Italy, Portugal [ 39 , 46 , 47 , 48 ], South Africa [ 49 ], and the USA [ 13 , 31 , 36 ]. The results obtained in our study provide valuable information related to the richness, occurrence, and pathogenicity of Botryosphaeriaceae species in association with citrus species.…”
Section: Discussionmentioning
confidence: 86%
“…7 "No" represents the relative locus was not successfully amplified in the current study. 8 "-" represents the relative locus was not amplified in the current study. 9 Isolates used for phylogenetic analyses.…”
Section: Aconidialismentioning
confidence: 78%
“…More than 40 species in the family have been reported on these trees from many different areas of the world (Farr & Rossman, 2019). Australia, South Africa and China are among those countries where extensive studies have been conducted on the Botryosphaeriaceae infecting Eucalyptus (Burgess et al, 2019; Jami et al, 2017; Li et al, 2020). To date, 17 species have been identified mostly from asymptomatic Eucalyptus spp.…”
Section: Introductionmentioning
confidence: 99%
“…In China, 11 species have been reported from die-back, leaf and shoot blight, stem and branch canker of Eucalyptus spp. (Li et al, 2020).…”
mentioning
confidence: 99%